Effects of mindfulness training and interference training on competitive shooting performance under stress - Xiao, J.; Liu, X.; Sun, J.; Zhang, T. (Applied & Educational Psychology, 2023)
We aimed to examine the effects of interference training and mindfulness training on the performance of shooting enthusiasts. 57 pistol shooting enthusiasts were equally distributed based on ability to an Interference Training Group (n=19 with mean age of 6.89±2.61; 10 males and 9 females), Mindful Training Group (n=19 with mean age of 16.26±2.57; 10 males and 9 females), and a Control Group (n=19 with a mean age of 16.73±2.10; 10 males and 9 females). A mixed experimental test with 3×6 repeated measures ANOVA was used to test outcomes. The between-group variable was psychological intervention (interference/mindfulness/control) and the within-group independent variable was time (T1-T6). The dependent variables included shooting task performance. The Five Facet Mindfulness Questionnaire, and Competitive State Anxiety Inventory-2. We found that interference training and mindfulness training significantly improved the participants' motor performance and mental state; the control group also showed some improvements. The improvement in shooting performance following interference training was fast but quickly plateaued. Conversely, following mindfulness training, the improvements were continuous and almost linear. Therefore, we suggested that athletes should choose mindfulness training as the main training method if adequate preparatory time is available before competition; we suggest interference training if less than one month's preparation time is available or in the context of inadequate professional psychological support.